Synthesis of Rapid Curing- High Resistance Polymeric Coating for Oil Tank Bases - كريمـد, زيدون خلف; اموري, د.قيــس مثنـى; ابراهيــم, بثينة خليـل; جبــر, هدى قاســم; عبد الكريم, ميس محمد; مجيد, حيــدر مظــفر (Journal of Petroleum Research and Studies, 2020)
Bottom base tank used in the storage of crude oil and oil derivatives are among the most exposure to the corrosion because its contact with corrosive media that causing corrosion of the metals despite the existence of cathodic protection this was monitored in most of the oil tanks spread throughout Iraq. In this sense، a polymeric self- hardening material derived from non epoxy primers was prepared it has high resistance to acid and high temperature by prepared resolsenol formaldehyde resin in basic media of sodium hydroxide and using plasticizer to give the elasticity to the polymer. The new polymer that synthesized identified by various spectral methods; such as FT-IR، 1H-NMR، 13C-NMR and thermal gravimetric analysis TGA/DTA. Topographic of the surface polymer also study by scanning electron microscope SEM and atomic force microscope AFM. One of the most important goals of this study was used the rapid curing high resistance polymer for bottom base oil tank coating. The efficiency and resistance of synthesized polymer were studied in several tests in acidic and basic media. Laboratory experiments have proven that the most efficient، effective and low cost is 1:3 and thickness 0.6 mm and resistance the pressure 5226.4 N and resistance to temperature up to 170 °C and resistance to acidic solution such as H2SO4 in different concentration. The economic cost of packing material was also studied where it was found that the cost of covering the base of a tank area 706.5 m2 estimated 4669.965 $.